EKSPRESI KREATIF SISWA SMA SANTO YOSEP SURAKARTA DALAM PELATIHAN TARI - Hartanto Hartanto (Abdi Seni, 2016)
This article talks about creative expression of students in SMA (Senior High School) Santo Yosep Surakarta in dance training. To gain the students’ creative expressions, the writer executes the following stages: dance appreciation, dance training, and implementation of their creative expressions into dance works. The creativity development is formed by gaining the student’s creative ability through the direct guiding. The students are given a freedom and discretion in body processing and express it in a performing art. This is supposed to give an understanding of creativity basic foundation, to form a creative media, to perform the creative works, and to document audio visual in order to be used as a reference in dance studying in Senior High School. Key words : creative expression, dance, student of Senior High School, and training.